1989
DOI: 10.1172/jci114249
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated phagocytosis in human neutrophils is associated with increased formation of inositol phosphates and diacylglycerol. Elevation in cytosolic free calcium and formation of inositol phosphates can be dissociated from accumulation of diacylglycerol.

Abstract: Phagocytosis of C3bi-or IgG-opsonized yeast particles in human neutrophils was found to be associated with an increased formation of inositol phosphates and diacylglycerol. Pertussis toxin only marginally affected phagocytosis of IgGand C3bi-opsonized particles and the associated formation of second messengers. Forskolin, which induced a threefold rise of cellular cAMP, however, markedly inhibited both C3bi-and IgG-mediated phagocytosis as well as the particle-induced formation of inositol phosphates and diacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 38 publications
0
29
1
Order By: Relevance
“…It was demonstrated that cAMP (via PKA activation) inhibited G-proteins [34], phospholipase C [35], inositol 1,4,5-triphosphate generation [35,36], formation of diacylglycerol [37], and release of Ca 2ϩ from intracellular storage organelles [36,38]. In this study, the failure of Ado to inhibit fMLPinduced Ca 2ϩ increase suggests that neither PLC-activated Ca 2ϩ release nor diacylglycerol (DAG) formation explains the reduction in O 2 Ϫ generation induced by fMLP.…”
Section: Discussionmentioning
confidence: 72%
“…It was demonstrated that cAMP (via PKA activation) inhibited G-proteins [34], phospholipase C [35], inositol 1,4,5-triphosphate generation [35,36], formation of diacylglycerol [37], and release of Ca 2ϩ from intracellular storage organelles [36,38]. In this study, the failure of Ado to inhibit fMLPinduced Ca 2ϩ increase suggests that neither PLC-activated Ca 2ϩ release nor diacylglycerol (DAG) formation explains the reduction in O 2 Ϫ generation induced by fMLP.…”
Section: Discussionmentioning
confidence: 72%
“…On the one hand, some studies have shown that the ingestion of insoluble immune complex mediated by FcgR was independent of IP 3 (23). On the other hand, IP 3 production has been found to be concomitant with FcgR activation (22,23). This discordance could be explained by the fact that IP 3 involvement in FcgR-mediated phagocytosis varies according to the cell type studied and the subclasses of FcgR activated by a given stimulus (insoluble immune complex or zymosan bioparticles).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IP 3 production has been associated with the mechanism of phagocytosis (21,22). In contrast, Rosales and Brown (23) excluded a role for the IP 3 pathway in FcgR-mediated particle internalization.…”
Section: Itpr1 and Itpr3 Are Involved In Igg-opsonized Zymosan Internmentioning
confidence: 99%
“…Their occupancy results in the G protein-dependent activation of several signaling pathways (PLC ␤ , adenylate cyclase, tyrosine phosphorylation) that lead to the generation of multiple second messengers including transient increases in the level of cytoplasmic free calcium (5,6). These are known to be involved in the initiation and modulation of several critical neutrophil responses including phagocytosis (7)(8)(9) and the activation of the NADPH oxidase (10 -12).…”
mentioning
confidence: 99%